Revenge of the dinosaurs. (Economist, 2001)
Distributed computing, which is about spreading processing power across several machines, often in different locations, was a reflection of the recent high-tech boom; but a number of technology analysts believe that there will be a renewed interest in mainframe computing given the economic downturn. Centralized computing could become popular again because of its lower costs. One way for companies to cut information technology costs is to get rid of their huge banks of server computers and run their applications more efficiently on mainframes instead. Companies such as Winnebago Industries, a maker of large motor-homes, and Korean Air have already begun to switch applications such as e-mail, keeping track of flight schedules, and revenue accounting from distributed systems back to mainframe programs.